2023
DOI: 10.3390/life13030670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Iron Parameters among Men Performing Regular Physical Activity—A Preliminary Study

Abstract: Iron deficiency anemia is one of the most common issues in clinical practice. It can be caused by intense physical activity, among other things. The aim of the study was to assess serum iron parameters in a group of men who engage in regular physical activity. The study group was composed of 20 men who regularly perform strength or endurance sports, whereas the control group consisted of 20 men without any sports activity. The red blood cell (RBC) parameters, platelet count (PLT), and white blood cell (WBC) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some studies have shown an association between physical activity and iron biomarkers which differed between sexes. Zamelska et al in 2023 found that lower serum ferritin concentration concerns men with regular physical activity [ 37 ]. In our study, further adjustment for physical activity did not materially change our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an association between physical activity and iron biomarkers which differed between sexes. Zamelska et al in 2023 found that lower serum ferritin concentration concerns men with regular physical activity [ 37 ]. In our study, further adjustment for physical activity did not materially change our findings.…”
Section: Discussionmentioning
confidence: 99%